2013
DOI: 10.1080/02699931.2012.762900
|View full text |Cite
|
Sign up to set email alerts
|

Are emotion impairments unique to, universal, or specific in autism spectrum disorder? A comprehensive review

Abstract: There is widespread belief that individuals with autism spectrum disorders (ASDs) are "emotionally detached" from others. This comprehensive review examines the empirical evidence for this assumption, addressing three critical questions: (1) Are emotion-processing impairments universal in ASD? (2) Are they specific, or can they be explained by deficits in other domains? (3) Is the emotion processing profile seen in ASD unique to these conditions? Upon review of the literature (over 200 studies), we conclude th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
104
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(119 citation statements)
references
References 147 publications
12
104
0
Order By: Relevance
“…That no significant group differences were found for non-negative emotions leads to conclude that the valence (and intensity) of an emotion affects recognition performance by individuals with ASD. This result is consistent with the literature, as valence and intensity are reported in a literature review as core factors influencing recognition performance specifically in ASD (Nuske et al, 2013). The results from the current study are in line with reports that the emotion recognition deficits in ASD are particularly evident for negative basic emotions (Ashwin et al, 2006;Gaigg, 2012;Wallace et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…That no significant group differences were found for non-negative emotions leads to conclude that the valence (and intensity) of an emotion affects recognition performance by individuals with ASD. This result is consistent with the literature, as valence and intensity are reported in a literature review as core factors influencing recognition performance specifically in ASD (Nuske et al, 2013). The results from the current study are in line with reports that the emotion recognition deficits in ASD are particularly evident for negative basic emotions (Ashwin et al, 2006;Gaigg, 2012;Wallace et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…Facial expressions of emotion are one form of non-verbal communication, and the ability to infer emotional states from facial expressions has been a major research interest in ASD. Literature reviews and meta-analyses have reported deficits in facial emotion recognition in ASD compared to controls (see Gaigg, 2012;Harms, Martin, & Wallace, 2010;Lozier, Vanmeter, & Marsh, 2014;Nuske, Vivanti, & Dissanayake, 2013;Uljarevic & Hamilton, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The existence and extent of emotional impairments in ASD has become a debated topic. Recent reviews indicate that individuals with ASD indeed have difficulty in processing emotional stimuli, but it is still debated whether those difficulties are secondary to other cognitive domains or constitute an independent problem (Nuske et al 2013;Gaigg 2012). Our results support the theoretical position that emotional impairments extend beyond the visual domain to emotional language and are a relatively independent component of ASD.…”
Section: Discussionsupporting
confidence: 80%
“…In contrast, other scholars argued that emotional impairments are more widespread and extend beyond the social domain (e.g., Gaigg 2012). Yet other authors argue that emotional impairments are not universal in ASD, which means that there is a lot of heterogeneity in the results across different groups of ASD participants and across different tasks, and that the impairments are not specific to emotion (Nuske et al 2013). This implies that many of the findings can be accounted for in terms of differences in attention/motivation/baseline physiological activity between ASD and comparison groups.…”
Section: Introductionmentioning
confidence: 99%
“…As compare to TD's, ASD's are insufficient for facial emotions learning. Most of the literature had reported ASD's with deficit in facial emotion recognition as compared to TD's [2,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%